Inter-comparisons of Spatially Interpolated Short-term and Long-term PM2.5 Concentrations of Local Authorities in South Korea 2015~2017 - Son, Kyuwon; You, Seunghee; Kim, Hyun Cheol; Kim, Byeong Uk; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2020)
Current national air quality improvement plans are supposed to lower long-term (annual mean) PM2.5 concentrations by strictly regulating domestic emissions. However, it is not clear if they can mitigate the frequency of PM2.5 exceedance days since short-term (daily mean) air quality largely depends on meteorological conditions. In this study, we evaluate the relationship between annual mean PM2.5 concentrations and frequency of daily mean PM2.5 exceedances at local authorities in South Korea based on spatially interpolated PM2.5 data from the urban air quality monitoring network during the recent 3 years (2015~2017). Correlation and slope between long-term PM2.5 concentrations and frequencies of daily mean PM2.5 exceedance (>35 μg/m3) for provinces of which annual mean PM2.5 concentrations were higher than 23 μg/m3 was 0.89 and 9.9 days/μg/m3, respectively. It implies that countermeasures to alleviate the long-term PM2.5 concentrations would be effective to reduce the number of the short-term exceedances and vice versa. However, for the elevated daily mean PM2.5 concentrations (>50 or 75 μg/m3), the correlation (slope) reduced to 0.80 (4.65) and 0.57 (0.7), respectively. This result exhibits that domestic emission control may not be effective to reduce the frequency of those high PM2.5 days. Jeonbuk showed the highest annual mean PM2.5 concentration during the 3 years while the maximum differences in annual mean PM2.5 concentrations and the daily PM2.5 exceedances between basic local authorities in South Korea was 19.1 μg/m3 and 116 days/year, respectively, during the years.
Keywords: Annual mean; Correlation; Daily exceedance; Local authority; PM2.5; Province